Materials and technologies for green construction - Kamal, Mohammad Arif (Key engineering materials, 2015)
The need of today is to have energy efficient buildings materials andconstruction technologies that cater to this rising need. Hence, selectingconstruction and finishing materials that have low embodied energy and haveless operational and maintenance cost is the most powerful tool for thearchitects, designers and the constructors to achieve high energy efficiencyin buildings. This special volume on 'Materials and Technologies for GreenConstruction' contains Ten chapters which address a wide range of issuespertaining to building materials and technologies with reference to energyefficiency. Thi.